The Guman of Dumalinao. [anthology].
A traditional "buklog" or feast is held to celebrate the union of the two kingdoms. "Guman" is an epic of the Suban-on tribe who inhabit the highlands of Northwestern Mindanao, in the territory that is now partitioned among the three provinces of Misamis Occidental, Zamboanga del Norte, and Zamboanga del Sur.